2022
DOI: 10.7759/cureus.22550
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Vancomycin and Gentamicin for Intraoperative Presoaking of Hamstring Graft in Primary Anterior Cruciate Ligament Reconstruction

Abstract: IntroductionPostoperative infection is an uncommon complication with grave consequences following anterior cruciate ligament reconstruction (ACLR). Presoaking of the hamstring graft with antibiotics results in a lower rate of infection. The purpose of the current study was to compare the efficacy of two commonly used antibiotics, vancomycin and gentamicin, in reducing infection rates following anterior cruciate ligament reconstruction. MethodsThe retrospective study included a total of 578 patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…There is also the added benefit of reduced systemic effects and initial less renal excretion, ease of administration, and possible cost-effectiveness in prevention of PJI [ 5 ]. Direct application of antibiotic has been effectively used to reduce infections in spinal [ 6 ], anterior cruciate [ 7 ], trauma surgery [ 8 ], and in rat models [ 9 ]. Furthermore, there is a growing body of evidence for its use in TJR, with a number of reviews suggesting IAA importance [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…There is also the added benefit of reduced systemic effects and initial less renal excretion, ease of administration, and possible cost-effectiveness in prevention of PJI [ 5 ]. Direct application of antibiotic has been effectively used to reduce infections in spinal [ 6 ], anterior cruciate [ 7 ], trauma surgery [ 8 ], and in rat models [ 9 ]. Furthermore, there is a growing body of evidence for its use in TJR, with a number of reviews suggesting IAA importance [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…The American Journal of Sports Medicine 2024;52(4):956-960 DOI: 10.1177/03635465231223138 Ó 2024 The Author(s) ACLR surgery. 2,10 Both adult and pediatric formulations of gentamycin are frequently in shortage; however, some Canadian medical centers replaced gentamycin with tobramycin during the shortage period. 13,19 Tobramycin is another possible alternative to vancomycin, and both are already used in orthopaedic applications.…”
mentioning
confidence: 99%
“…Gentamycin solution is one such possible alternative and has recently been reported to help decrease the incidence of septic arthritis after ACLR surgery. 2,10 Both adult and pediatric formulations of gentamycin are frequently in shortage; however, some Canadian medical centers replaced gentamycin with tobramycin during the shortage period. 13,19 Tobramycin is another possible alternative to vancomycin, and both are already used in orthopaedic applications.…”
mentioning
confidence: 99%
“…Multiple meta-analyses showed that vancomycin soaking of the ACL graft can drastically reduce the incidence of postoperative septic knee arthritis after ACL reconstruction. 2,14,17,32 However, reservations regarding this method still prevail, and in 2021, two-thirds of the members of the prestigious ACL Study Group reported that they do not soak ACL grafts in vancomycin before implantation. 33 The most common concerns are vancomycin-induced weakening of the graft and chondrotoxicity.…”
mentioning
confidence: 99%
“…Multiple meta-analyses showed that vancomycin soaking of the ACL graft can drastically reduce the incidence of postoperative septic knee arthritis after ACL reconstruction. 2 , 14 , 17 , 32 …”
mentioning
confidence: 99%